Opetusavustaja opettajana – opiskelijakokemuksia opetusavustajan vaikutuksesta oppimisilmapiiriin ja ohjauksen laatuun oikeustieteen opetuksessa - Mielityinen, Sampo; Fifield, Aurora (Lakimies, 2024)
Teaching assistant as a co-teacher – students’ experiences of the effect of a teaching assistant on the learning atmosphere and the quality of instruction In Finnish law faculties, it is fairly common to have students working as teaching assistants in different roles and tasks. Their role as co-teachers and the effect this might have on different aspects of the learning environments and processes has not been studied before. Previous studies have identified several areas in need of development in Finnish legal education such as instruction and feedback for students, learning environments, interaction between the teacher and the students, as well as the approachability of teachers. The article focuses on two questions: 1) How do law students experience the effect of the teaching assistant as a co-teacher on the learning atmosphere? 2) How do law students experience the effect of the teaching assistant as a co-teacher on the quality of instruction? The analysis is based on a survey, collected from 63 first-year law students who participated in an obligatory course on legal decision-making. The article’s main conclusion is that the students’ views on the teaching assistant’s effect on learning atmosphere and quality of instruction were very positive. According to the students, the teaching assistant improved the mood of the course, made it easier for the students to ask questions and request advice, and provided extra content and guidance, making the materials and instructions at the same time more understandable and useful. The students also considered the teaching assistant as encouraging and identifiable. All in all, giving law students a role as co-teachers seems to be a promising way to tackle many development needs in Finnish legal education.